Dose-response risks of all-cause, cancer, and cardiovascular disease mortality according to sex-specific cigarette smoking pack-year quantiles - Jieun Hwang; Suyoung Jo; Heewon Kang; Eunsil Cheon; Sung-il Cho (Tobacco Induced Diseases)
Introduction This study investigated the risks for all-cause death and death from cancer or cardiovascular diseases due to smoking status and behavior, focusing on differences in smoking duration and amount stratified by sex.